Performance harmony between the inner feeling and the external movement of the actor on stage - Ali Khudair Muhammad ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2021)
The problem of research lies in the mechanism of harmony and its understanding, and understanding its necessity, without which the creative process collapses on the stage or becomes more like a failure, then the problem of research in researching the problem of performance harmony comes as a mechanism, elements, application, importance and influence on the recipient and the theatrical work in general, and we focus on the nature of harmony and the ability of the actor to Reaching it and its impact on reaching the recipient and leaving the necessary creative impact, and thus the success of the creative process and the achievement of a chemical movement par excellence.